THE DIAGNOSTIC VALUE OF TROPONIN I TESTING TO CORONARY ANGIOGRAPHY WITH A POINT OF CARE TESTING INSTRUMENT IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - Riska Anton; Sheila Febriana; Asvin Nurulita; Uleng Bahrun (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Myocardial infarction consists of STEMI and NSTEMI. Acute myocardial infarction is diagnosed by WHO criteria when at least two of the following three criteria are met: chest pain, electrocardiography (ECG) result changes, and biomarker. Troponin I is specific for cardiac muscle and has an increased level even in small cardiac muscle necrosis and not affected by the renal failure and muscle trauma but have not been standardized by WHO. This research aimed to find the effectivity of Troponin I examination with POCT to help the diagnosis and early detection of AMI. Thus each product has varied sensitivity and specificity. A cross-sectional study was conducted in the Clinical Pathology Laboratory and Cardiac Center of the Dr. Wahidin Sudirohusodo Hospital Makassar using suspected AMI patients as the subject. Troponin I level tested by POCT from August 2015 to July 2016. Data were analyzed statistically using the ROC curve with SPSS software. A total of 88 patients suspected with AMI, aged 36 to 75 years old. From the tested cut-off values (0.02, 0.03, 0.04, 0.5, 0.06, 0.07, 0.08 μg/L) the best cut-off value was 0.03 μg/L (93.9% sensitivity, 95.5% specificity, PPV 98.4%, NPV 84.0%, and 94.3% accuracy) where the cut-off value of 0.03 μg/L was the value recommended by the toolkit manual. Even if the cut-off value of 0.02 or 0.04 was used, the sensitivity and specificity value was still fairly good. Troponin I testing using POCT with a cut-off value of 0.03 μg/L can be used routinely in supporting the AMI diagnosis because it is a rapid test with a portable instrument and excellent diagnostic value.